ANALISIS KARAKTERISTIK DAN PENDAPATAN PETANI ANGGOTA KOPERASI ANUGRAH MULIA YANG MENJUAL HASIL OLAHAN KARET KERING DAN KARET BASAH DI KECAMATAN TALANG UBI KABUPATEN PALI - Santoso, Tomi Wahyu; Kurniawan, Rahmat (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
This study aims to determine the characteristics of farmers who sell dry rubber and wet rubber and to find out how much income farmers get from selling dry rubber and wet rubber and what are the factors that influence farmers who sell dry rubber and wet rubber in Talang Ubi District Penukal Abab Lematang Ilir (PALI). Regancy, South Sumatera Province. The sampling method used was disproportionate stratitifed ramdom sampling with rubber farmer respondents in Talang Ubi District. Data collection techniques used in this study were observation and direct interviews with respondents using tools in the form of a list of questions that had been prepared in advance. The data analysis method used in quantitative descriptive analysis. The number of respondent in this study were 54 farmers. From the research results, it was found that the characteristics of farmers who sell dry rubber are influenced by education, selling price, number of family members and income, while wet rubber farmers are influenced by age and land area. Based on the results of the study note that the average income of farmers dry rubber is Rp. 12.135.160./lg/month. While the average income of farmers who sell wet rubber is Rp. 9.859.225/lg/month. And the factor that influenced farmers to prefer selling dry rubber to wet rubber was the higher selling prince of dry rubber.